The Influence of Financial Performance, Debt Level, and Sales Growth on Tax Avoidance in Indonesian Banking Companies (2019–2023) - Kartika, Lina Tri; Asrorudin, A (Yayasan Pendidikan Penelitian Pengabdian Al-amsi, 2025)
This study examines the influence of financial performance, debt level, and sales growth on tax avoidance in banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A quantitative approach was employed using purposive sampling to select 7 companies that met the criteria, resulting in 35 observations after removing outliers for normality. The data were analyzed using panel data regression with the Common Effect Model and processed using EViews 12. The findings show that financial performance has a significant negative effect on tax avoidance, while debt level and sales growth do not have significant effects. The adjusted R-squared value of 52.16% indicates that the independent variables explain more than half of the variation in tax avoidance. These results contribute to the understanding of tax avoidance behavior in the banking sector and offer insight for regulators in designing tax compliance policies.